Macrophage Migration Inhibitory Factor Regulates U1 Small Nuclear RNP Immune Complex–Mediated Activation of the NLRP3 Inflammasome - Shin, Min Sun; Kang, Youna; Wahl, Elizabeth R.; Park, Hong‐Jai; Lazova, Rossitza; Leng, Lin; Mamula, Mark; Krishnaswamy, Smita; Bucala, Richard; Kang, Insoo (Arthritis & rheumatology (Hoboken, N.J.), 2019)
Objective High‐expression alleles of macrophage migration inhibitory factor (MIF) are linked genetically to the severity of systemic lupus erythematosus (SLE). The U1 small nuclear RNP (snRNP) immune complex containing U1 snRNP and anti–U1 snRNP antibodies, which are found in patients with SLE, activates the NLRP3 inflammasome, comprising NLRP3, ASC, and procaspase 1, in human monocytes, leading to the production of interleukin‐1β (IL‐1β). This study was undertaken to investigate the role of the snRNP immune complex in up‐regulating the expression of MIF and its interface with the NLRP3 inflammasome. Methods MIF, IL‐1β, NLRP3, caspase 1, ASC, and MIF receptors were analyzed by enzyme‐linked immunosorbent assay, Western blotting, quantitative polymerase chain reaction, and cytometry by time‐of‐flight mass spectrometry (CytoF) in human monocytes incubated with or without the snRNP immune complex. MIF pathway responses were probed with the novel small molecule antagonist MIF098. Results The snRNP immune complex induced the production of MIF and IL‐1β from human monocytes. High‐dimensional, single‐cell CytoF analysis established that MIF regulates activation of the NLRP3 inflammasome, including findings of a quantitative relationship between MIF and its receptors and IL‐1β levels in the monocytes. MIF098, which blocks MIF binding to its cognate receptor, suppressed the production of IL‐1β, the up‐regulation of NLRP3, which is a rate‐limiting step in NLRP3 inflammasome activation, and the activation of caspase 1 in snRNP immune complex–stimulated human monocytes. Conclusion The U1 snRNP immune complex is a specific stimulus of MIF production in human monocytes, with MIF having an upstream role in defining the inflammatory characteristics of activated monocytes by regulating NLRP3 inflammasome activation and downstream IL‐1β production. These findings provide mechanistic insight and a therapeutic rationale for targeting MIF in subgroups of lupus patients, such as those classified as high genotypic MIF expressers or those with anti‐snRNP antibodies.